The Influence of Fear of Missing Out Shopping Lifestyle and Promotion on Impulsive Buying of iPhone Products in Gen Z in the City of Surabaya - Rizky Arya Maulana (Journal of Behavioral Economics, Finance, and Management Insights, 2025)
The rapid development of technology and intense business competition have significantly influenced consumer behavior, particularly among Generation Z who dominate mobile phone ownership in Indonesia and exhibit unique consumption patterns toward premium brands like iPhone. This study analyzes the influence of Fear of Missing Out (FOMO), shopping lifestyle, and promotion on impulsive buying behavior for iPhone products among Generation Z in Surabaya. Utilizing a sample of 150 respondents drawn from the Surabaya-based Generation Z population through purposive sampling, the research employed online questionnaires with a Likert scale for data collection. Subsequent analysis via Multiple Linear Regression using SPSS 27 yielded partial results showing that: (1) FOMO does not have a significant effect on impulsive buying (sig. 0.751 > 0.05); (2) shopping lifestyle has a positive and significant effect (sig. 0.001 < 0.05); and (3) promotion has a positive and significant effect (sig. 0.043 < 0.05). Simultaneously, all three variables significantly affected Impulsive Buying with an R Square contribution of 12.3%. In conclusion, while Gen Z follows iPhone trends, FOMO is not the primary driver of impulsive purchases. Instead, shopping lifestyle and promotions play dominant roles in encouraging unplanned purchases. Marketers should optimize creative promotional strategies over FOMO-based approaches.